Implementation of Natural Phenomena Theme Collage Activities in Early Childhood Learning - Fadilah Utami; Aghnaita Husain; Muzakki Muzakki (Southeast Asian Journal of Islamic Education, 2022)
Early childhood is a sensitive period in which the process of child growth and development will also affect the next period. One form of stimulation that can be given by teachers in early childhood is through natural environment materials, such as the introduction of natural phenomena both naturally and as a result of humans. The introduction of natural phenomena at an early age can be done by making learning themes and formulating several related materials and sub-themes. One of them is the volcano sub-theme through collage activities. The purpose of this study was to describe the implementation of collage activities on the theme of natural phenomena in early childhood learning. The method used in this study was a qualitative descriptive with the subject of the study, namely the teacher of class B RA Al-Muslimun Nurul Islam Palangka Raya. Data collection techniques used observation and interview techniques. The results of the study showed that the collage activity consists of several stages, including planning the image to be made, preparing tools and materials, introducing equipment and techniques, providing guidance to children, and explaining the position when pasting, and repeating the exercise. This activity can also introduce natural phenomena to children in a simple way, foster children's interest in the world of science, train children's awareness of emergencies, and develop other various aspects of child development.